O lugar da arquitetura no inventário alagoano de referências culturais - Juliana Michaello Macêdo Dias; Roseline Vanessa Santos Oliveira (Confins)
The article discusses the place of architecture as a cultural patrimony between its materiality and the fluidity of the immaterial relations constructed with them from the different social groups. These bonds, built by people in daily life and rooted in traditions, allow us to observe new ways of looking at built heritage. As a result of the experiences accumulated over two years of extensive field research throughout Alagoas, in the Safeguarding of the Intangible Heritage of Alagoas Project, the central question of the article is how these other perspectives can stimulate new practices in the heritage discussion.